El portal noticioso “La Cátedra Deportes” en la red social Tik Tok y su evolución en la cobertura periodística deportiva (2023-2024) - Anchante Pinillos, Matias Mauricio (2025)
This professional proficiency report, prepared by Fairux Cabrera and Dessire Navarro, documents and analyzes Cabrera's professional experience in the communications department of the Office of Civil Defense and Citizen Security (GRDNDCYSC) of the Callao Regional Government (GORE). This experience focused on his participation in the development of the "Disaster Risk Management Campaign," carried out between November and December 2024. The central focus of this report is an analysis of the value of traditional communication and journalists in campaigns that seek to strengthen the culture of prevention in vulnerable areas, especially under the guidelines of Budgetary Program 0068 (PP 0068). The investigation details the tactics the journalist implemented with the unit's communications team. All of these activities were implemented with the goal of raising public awareness about the importance of emergency preparedness and response in highly vulnerable districts such as Mi Perú, Ventanilla, and Callao. The report also includes an analysis of the campaign's communication impact, addressing factors such as public response, the adaptation of the message to the profile of the Callao population, and the obstacles that influenced message reception. It also analyzes the specific characteristics of implementing DRM campaigns in Callao, the need to strengthen the institutional continuity of these efforts, and the implementation of tools to measure their real reach.